Psikoterapi Profetik Sebagai Islamic Helping Relationship - Kusumastuti, Wanodya; Nasrudin, Nasrudin (Universitas Muhammadiyah Metro, 2024)
The current Islamic psychotherapy model has developed a lot and effectively overcame various human problems. One type of study of Islamic psychotherapy is prophetic psychotherapy. This study aims to examine and analyze the concept of prophetic psychotherapy, which is a part of Islamic psychotherapy. Studies on prophetic psychotherapy are still restricted, so implementation in psychotherapy practice is not yet felt. Therefore, this research is essential to discuss the study of prophetic psychotherapy from various sources so that it can become a reference for developing the field of study of prophetic psychotherapy that many groups can utilize. This research collects multiple sources of literature that are relevant to search media from digital platforms. The collected data will be analyzed using the PRIMA flowchart and charting data to describe the concept and study of prophetic psychotherapy fully; more specifically, this study will discuss the study of prophetic psychotherapy as a method of Islamic helping relationships. The literature sampling technique used is a scoping review, namely categorizing relevant articles, making concept maps, and analyzing the review results. The study results show that Islamic psychology has a broad scope, not only in the context of psychotherapy but also in counseling. Prophetic counseling and psychotherapy have basic principles in applying interventions: recitations, tazkiyah, Salim, uswah Hashanah, and awareness. These basic principles can be used by individuals so that they can increase their faith, moral understanding, and psychological well-being, become a whole person, and submit to Allah SWT.